HUBUNGAN JENIS KELAMIN, PERILAKU MEROKOK, AKTIVITAS FISIK DENGAN HIPERTENSI PADA PEGAWAI KANTOR[Correlation of Sex, Smoking Habit, Physical Activity and Hypertension among Offi ce Employee] - Eganda Garwahusada; R. Bambang Wirjatmadi (Media Gizi Indonesia, 2020)
Hypertension is known as the silent killer. Hypertension can be caused by non-modifi able factor such as gender and modifi able factor such as smoking habit and physical activity. Purpose of this study was to examine the relationship between gender, smoking habit, and physical activity with hypertension among offi ce employees in Provincial Public Health Offi ce of Central Java. This study used case control design. This case control study included 46 offi ce employee, divided into 23 cases and 23 controls who were taken using simple random sampling. Data were collected by interview, fi lling IPAQ questionnaire, and blood pressure measurement. Data were analyzed using Chi-Square test. This study revealed that most of the employee are woman (54,3%), did not smoking (73,9%), and had a high physical activity level (65,2%). There was a signifi cant relationship between gender (p value=0.003, OR=8.229; 95% CI:2.175-31.132) and smoking habit (p value=0.019, OR=8.077; 95% CI=1.523-42.834) with hypertension. Whereas physical activity (p=0,122) was not in a signifi cant relationship with hypertension. It is concluded that male smoking employees tend to have hypertension. It is recommended for employees to stop smoking and increasing physical activity to reduce the risk of hypertension.